Covalent and Non-covalent Noble Gas Bonding Interactions in XeFn Derivatives (n = 2–6): A Combined Theoretical and ICSD Analysis - Gomila, Rosa M.; Frontera, Antonio (Frontiers in Chemistry, 2020)
A noble gas bond (also known in the literature as aerogen bond) can be defined as the attractive interaction between any element of group-18 acting as a Lewis acid and any electron rich atom of group of atoms, thus following the IUPAC recommendation available for similar π,σ-hole interactions involving elements of groups 17 (halogens) and 16 (chalcogens). A significant difference between noble gas bonding (NgB) and halogen (HaB) or chalcogen (ChB) bonding is that whilst the former is scarcely found in the literature, HaB and ChB are very common and their applications in important fields like catalysis, biochemistry or crystal engineering have exponentially grown in the last decade. This article combines theory and experiment to highlight the importance of noncovalent NgBs in the solid state of several xenon fluorides [XeFn]m+ were the central oxidation state of Xe varies from +2 to +6 and the number of fluorine atoms varies from n = 2 to 6. The compounds with an odd number of fluorine atoms (n = 3 and 5) are cationic (m = 1). The Inorganic Crystal Structural Database (ICSD) strongly evidences the relevance of NgBs in the solid state structures of xenon derivatives. The ability of Xe compounds to participate in π,σ-hole interactions has been studied using different types of electron donors (Lewis bases and anions) using DFT calculations (PBE1PBE-D3/def2-TZVP) and the molecular electrostatic potential (MEP) surfaces.